2009
DOI: 10.1186/1475-925x-8-19
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear dielectric spectroscopy of microbiological suspensions

Abstract: Background: Non-linear dielectric spectroscopy (NLDS) of microorganism was characterized by the generation of harmonics in the polarization current when a microorganism suspension was exposed to a sinusoidal electric field. The biological nonlinear response initially described was not well verified by other authors and the results were susceptible to ambiguous interpretation. In this paper NLDS was performed to yeast suspension in tripolar and tetrapolar configuration with a recently developed analyzer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…[6][7][8]. Fortunately, in our previous study, we performed measurements with different cells and obtained relevant results with the three-electrode cell [9]. Our results indicated that the changes in the third harmonic were due to the presence of microorganisms near the EEI [9], where they were consistent with Blake-Coleman's results [10].…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…[6][7][8]. Fortunately, in our previous study, we performed measurements with different cells and obtained relevant results with the three-electrode cell [9]. Our results indicated that the changes in the third harmonic were due to the presence of microorganisms near the EEI [9], where they were consistent with Blake-Coleman's results [10].…”
Section: Introductionsupporting
confidence: 84%
“…Fortunately, in our previous study, we performed measurements with different cells and obtained relevant results with the three-electrode cell [9]. Our results indicated that the changes in the third harmonic were due to the presence of microorganisms near the EEI [9], where they were consistent with Blake-Coleman's results [10]. In all of these studies, it was not indicated whether the changes in the amplitude of the third harmonic originated in changes in the double-layer capacity or in charge transfer resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It requires a measurement system with a robust feature to resist artificial and environmental noises, especially in cases of low sample cell concentrations. Among numerous methods, dielectric spectroscopy (DS) based on probes or electrodes has been a common choice for biomass measurement and monitoring due to its advantages of fast, simple, and low-cost features [24,25,26]. However, invasive or contact sensors in these DS systems could lead to serious measurement errors and even contaminate and damage samples under test.…”
Section: Introductionmentioning
confidence: 99%
“…Treo and co-workers did measurements with an improved nonlinear dielectric spectrometer and three different electrochemical cells (Treo et al, 2005;Treo and Felice, 2009). One of them was a replica of that used by Woodward and Kell, and the other two were three-and four-electrode cells respectively.…”
Section: Introductionmentioning
confidence: 99%